TINJAUAN YURIDIS PERLINDUNGAN HUKUM BAGI PELAKU PELECEHAN SEKSUAL DI INDONESIA - Bentri Nelci Sabloit (The Juris, 2026)
Sexual harassment is a crime that has far-reaching impacts on victims physically, psychologically, and socially. While the state has an obligation to protect victims, under Indonesia's criminal justice system, which adheres to the principle of dufe process of law, legal protection is also afforded to perpetrators. This study aims to examine the forms of legal protection granted to perpetrators of sexual harassment, the legal basis for such protection, and its implications for the principle of justice. The method used is normative juridical with a doctrinal approach through literature study. The findings indicate that perpetrators retain legal rights, such as access to legal assistance, fair trial, and humane treatment, as guaranteed by the 1945 Constitution, the Criminal Procedure Code (KUHAP), and other relevant regulations. However, in practice, these rights are often violated through stigma, vigilantism, and unfair treatment. Legal protection for perpetrators is not intended to justify their actions, but rather to ensure a fair and civilized legal process in accordance with human rights principles.